A journey of acculturation and growth: An autoethnography of an international counseling psychologist in training - Xie, Qiang; Jiwani, Zishan; Goldberg, Simon B. (Journal of International Students, 2026)
The experiences of international counseling psychology students (ICPS) across multiple domains of training and their professional identity development were under-investigated. To address this gap, this study used autoethnography to explore the implications of international student identity for one ICPS with a lower socioeconomic background and first-generation college student status. Guided by an open-ended research question, this autoethnography was developed through an iterative, narrative-driven process. Personal and professional sources supported the writing process. Three recurring areas of experience emerged: (1) Adjustment Challenges Related to International Student Identity, (2) Strengths Tied to International Student Identity, and (3) Developing a Social Justice-Oriented Professional Identity through Lived Experience and Training as an ICPS. The findings highlight minority stress experienced by ICPS and the dialectical coexistence of challenges and strengths in their training. Recommendations are provided to professional organizations, training programs, and mentors to enhance culturally responsive training for ICPS.